THE ROLE OF EDUCATION, JOB ANALYSIS, AND WORK TENURE ON EMPLOYEE PERFORMANCE FOR FILLING STRUCTURAL POSITIONS - Warto, Warto; Sriyono, Sriyono; Setiyono, Wisnu Panggah (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2025)
In order to ensure the effective placement of structural positions, good judgment is required to ensure productivity and operational efficiency. This study analyzes factors such as education, job analysis, and tenure, which may affect employee performance to fill structural positions in PLTU Asam-Asam. Methods used are quantitative and perform hypothesis testing by utilizing Structural Equation Modeling - Partial Least Squares (SEM PLS). The population in this study is 183 PLTU Asam-Asam employees, and the entire population will be used as research subjects. The study's findings revealed that education, job analysis, and work tenure had a positive and significant influence on employee performance, both partially and simultaneously. This study concluded that to improve employee performance for structural position fulfillment, it is necessary to pay attention to the combination of relevant educational background, comprehensive job analysis, and appropriate work tenure. The suggested policies are to increase competency-based training programs, improve the job evaluation system, and adopt a merit-based promotion policy to ensure alignment between an individual and the targeted structural position.